Community Empowerment Practices Based on Mawah Local Wisdom in the Cattle Fattening System at the PT PHE NSO Assisted Breeder Group - Putra, Nurseno Dwi; Vernanda, Rani Noor; Ulfah, Nurhayatul (Catalist Indo Publisher, 2025)
Background The consumption of meat in Aceh Province is among the highest in Indonesia. However, this condition is not supported by cows farming practices, which are still managed traditionally. The cow fattening and breeding programs are strategic efforts to improve the economic welfare of rural communities, including in Aceh Province. Additionally, the Acehnese community possesses local knowledge and practices known as 'MAWAH,' which can be utilized as a system to enhance economic welfare in the livestock sector. Mawah is a traditional practice that involves cooperation between capital owners and local farmers, allowing for the fair and sustainable distribution of profits. PT Pertamina Hulu Energi (PHE) - NSO has integrated these elements into its Corporate Social Responsibility (CSR) program named SAPIKU. This study aims to analyze the sustainability and conditions of the SAPIKU Program. Methods The approach used in this research is a qualitative approach with methods of observation and literature review. The qualitative data analysis involves identifying patterns and factors that influence the success of the program. Results The results show that the active participation of the community, village government, and the company are key factors in the program's success. Conclusions The SAPIKU program should apply sustainable and innovative approaches, such as livestock technology and efficient management, to improve economic and environmental impacts. This strategy will support farmers' welfare and meet long-term beef demand.